Transition to maternity/paternity and rearing practices in three generations - Robles Estrada, Erika; Oudhof van Barneveld, Hans; Mercado Maya, Aída (Pensando Psicología, 2019)
Objective: To analyze the transition to maternity / paternity and the perception of parenting practices in three generations of 18 men and women from the city of Toluca, Mexico.Methodology: In-depth interviews were performed and the phenomenological method was used for the analysis of the information.Results: Certain elements remained constant during the transition to maternity / paternity between generations, such as the practice of nurturing the promotion of good relationships between siblings. Dynamic aspects included taking care of physical and mental health, coercive control and school support. The constant practice in the first two generations and dynamic in the third, was to teach the role of girl or boy.Conclusions: It is concluded that the transition to maternity / paternity is an internal process, while parenting practices depend on the sociocultural context.
Keywords: maternity; paternity; parenting practices